Implementasi Metode Problem Solving dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam di SMA Negeri 3 Purwakarta: Studi Eksperimental pada Kelas X - Wishal, Wishal Luthfikha; Tabroni, Imam; Saleh, Abdurahman (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This research was conducted to investigate the effectiveness of teaching methods in enhancing the learning outcomes of Islamic Religious Education (PAI) for 10th-grade students at Sekolah Menengah Atas Negeri 3 (SMAN 3) Purwakarta. This study aimed to compare the learning outcomes of students between the lecture method and the Problem-Solving method. The research method employed was an experiment involving two groups of students, namely the experimental group taught using the Problem-Solving method and the control group taught using the lecture method. Learning outcome data was collected through pre-tests and post-tests and analyzed using the Independent T-Test statistical analysis. The research results indicated that the Problem-Solving method significantly improved students' learning outcomes (mean=65.51) compared to the lecture method (mean=41.67). The average percentage of students' learning outcomes using the Problem-Solving method reached 81.89%, categorized as